Tibetan Medicine and You: A Path to Wellbeing, Better Health, and Joy - Cameron, Miriam E.; Namdul, Tenzin (Rowman & Littlefield Publishers, 2020)
All of us want to be happy and avoid suffering. So why are many of us anxious, angry, depressed? We suffer from pain, hypertension, inflammation, indigestion, insomnia, and addictions. Yet, too often we make choices that sabotage us rather than reverse what’s wrong. Tibetan medicine, Tibet’s ancient, comprehensive science of healing, offers effective tools for transforming suffering into health and happiness. Tibetan medicine teaches that the purpose of life is to be happy, and that after our basic needs are met, happiness results primarily from our own thinking. When challenges arise, we can wallow in negativity and get sick - or even sicker - in mind and body. Or we can decide to create health and happiness. Making positive choices won’t solve every problem but will produce better results than poor or thoughtless decisions do. This unique book explains in everyday English how to use Tibetan medicine for self-care and as a complement to modern medicine. Tibetan medicine sheds light on the intricate relationship between mind and body. Each of us is born with a unique combination of energies called our constitution. Understanding our constitution empowers us to make conscious, informed decisions about our thoughts, diet, and behavior to keep our energies in balance. We learn to reduce stress, create health, prepare for death, and be happy.